STUDY OF THE CONTEMPORARY ARCHITECTURE CONCEPT IN THE TSUNAMI ACEH MUSEUM BUILDING - Nursandi, Izwan Ariq; Ashadi, Ashadi (Border: Jurnal Arsitektur, 2021)
The museum building is a type of building that serves as a place of education and the knowledges place to introduce a history, events, creatures, etc. The purpose of the museum itself is to educate those things to the all generations in the future, so that the knowledges on a civilization will not be disconnected and disappear. As time passes, the museum building also has a diverse design architectures. One of them, concept of contemporary architecture style has its own style and not binding on a particular style. The museum building with the application of the contemporary architecture’s concept to make buildings with the characteristics of the distinctively and character. From that issue, arises the issue of how the application of the concept of contemporary architecture in the building of the museum. The aims of this research is to analyze the application of contemporary architecture in the Tsunami Aceh Museum building. The method used in this research is a descriptive qualitative method with the stages of the analysis based on characteristics of the contemporary architecture of the application in the case study museum building. The result on this research is a conclusion of the application of the concept of contemporary architecture to the museum.